Increasing Dairy Cows Productivity through New Balanced Concentrate Feed: A Study in Bihar, India - Singh, Dhiraj Kumar; Sahu, Shree Prasad; Teufel, Nils (Indian Journal of Animal Nutrition, 2019)
Dairying is an integral part of small-holder farming systems as well as an important source of subsidiary income for most households in Bihar, India. Nevertheless, the per-capita milk availability in Bihar is very low (228 g/d) compare to India average (355 g/d) in 2016-17 as productivity is low, mainly because current feeding is based mainly on crop residues. Constraints to improving these feeding practices include limited farm resources, weak support services and poor knowledge on nutrient requirements and contents. The present study examines the effect of a balanced feed on livestock productivity in Bihar, in comparison to existing feeding practices. Hereby, farmers supplement residues with either individual concentrate components or commercial feed. The new balanced feed consists of crushed grains (37%), cereal brans (30%), pulse husks (10%), oil cakes (20%) and minerals. This results in higher levels of metabolizable energy and digestibility compared to the other commercial feeds according to laboratory analysis. This new feed was introduced through a combination of participatory trainings on nutrition and feeding, demonstrations on feed preparation and farm-based feeding trials on 1040 crossbred dairy cattle. On average, farmers were feeding 4.0 kg commercial and/or home-made feed per dairy animal/day, adjusted to individual milk yields. After replacing the existing supplements with a reduced amount (3.4 kg) of new feed, average milk yield, fatÂ and SNF increased by 14%, 16% and 4%, respectively. Analysis suggests that dairy farmers can simultaneously reduce their cost of milk production and increase their revenue from increased milk sales. The new balanced feed also showed better palatability and positive effects on health and reproductive performance in terms of animal appearance and early conception. Finally, the new feed does not require cooking, a common practice. Methods are explored to disseminate this balanced concentrate feed to a larger section of farmers in the state.